High risk of respiratory diseases in children in the fire period in Western Amazon - Pãmela Rodrigues de Souza Silva; Eliane Ignotti; Beatriz Fátima Alves de Oliveira; Washington Leite Junger; Fernando Morais; Paulo Artaxo; Sandra Hacon (Revista de Saúde Pública, 2016)
ABSTRACT OBJECTIVE To analyze the toxicological risk of exposure to ozone (O3) and fine particulate matter (PM2.5) among schoolchildren.. METHODS Toxicological risk assessment was used to evaluate the risk of exposure to O3 and PM2.5 from biomass burning among schoolchildren aged six to 14 years, residents of Rio Branco, Acre, Southern Amazon, Brazil. We used Monte Carlo simulation to estimate the potential intake dose of both pollutants. RESULTS During the slash-and-burn periods, O3 and PM2.5 concentrations reached 119.4 µg/m3 and 51.1 µg/m3, respectively. The schoolchildren incorporated medium potential doses regarding exposure to O3 (2.83 μg/kg.day, 95%CI 2.72–2.94). For exposure to PM2.5, we did not find toxicological risk (0.93 μg/kg.day, 95%CI 0.86–0.99). The toxicological risk for exposure to O3 was greater than 1 for all children (QR = 2.75; 95%CI 2.64–2.86). CONCLUSIONS Schoolchildren were exposed to high doses of O3 during the dry season of the region. This posed a toxicological risk, especially to those who had previous diseases.